On creation of a cathode units for the X -band klystron using a high-current magnetron gun as a base - Dovbnya, A.N.; Ayzatsky, N.I.; Boriskin, V.N.; Zakutin, V.V.; Kushnir, V.A.; Mitrochenko, V.A.; Reshetnyak, N.G.; Perezhogin, S.A.; Stepin, D.L. (Вопросы атомной науки и техники, 2004)
The article presents the results from studies, performed at the R&D “Accelerator” NSC KIPT, on development of units for the X-band klystron with an output power 1...2 MW and at a voltage 50...100 kV. A magnetron
gun with a cold secondary-emission metallic cathode is supposed to be used as an electron source. Приведено результати досліджень, направлених на творення в НДК “Прискорювач” ННЦ ХФТІ вузлів
клістрона Х-діапазону з вихідною потужністю 1...2 МВт и напряженим 50...100 кВ для медичних
терапевтичних прискорювачів. В якості джерела електронів передбачається використання магнетронної
гармати з вторинно-емісійним холодним металевим катодом. Приведены результаты исследований направленных на разработку в НИК «Ускоритель» ННЦ ХФТИ
узлов клистрона Х-диапазона с выходной мощностью 1…2 МВт и напряжением 50…100 кВ для медицинских терапевтических ускорителей. В качестве источника электронов предполагается использовать магнетронную пушку с вторично-эмиссионным холодным металлическим катодом.